School Leadership Strategy to Increase Teacher Professionalism and Its Impact on the Quality of Learning Education at Marcelo 2 Comoro School - Isac , Pinto de Jesus (MultiTech Publisher, 2024)
The study aims to analyze the school director's strategy to increase teacher professionalism in basic education and its impact on improving the quality of learning. The research findings will build theories for the School Leadership Strategy, focusing on increasing teacher professionalism, which focuses on the quality of learning. The study will serve as a reference for the academic community and professionals to carry out continuous verification and discovery of this branch of science. Education is an inspiration for science, and a strong basic education can affect the future development of the nation. The leadership strategy consists of various ways to increase teacher professionalism, such as attitude, mentality, and intellectual capacity. The survey was conducted between July 31st and August 11th, 2023, in the Basic Education of Marcelo 2 Comoro Administrative Post of Dom Aleixo, Dili Municipality. The research findings show that leadership responds to the same purpose as teachers, aiming to improve the quality of teaching learning through various ways to increase teacher professionalism. The steps used by leadership to improve the quality of teacher professionalism through academic training and the leadership strategy are used to facilitate teachers at different levels of education to ensure quality.